Atribut Destinasi, Persepsi Risiko, Kepercayaan, dan Niat Berkunjung Wisatawan ke Pulau Nusa Penida Klungkung Bali pada Masa Pandemi Covid-19 - I Wayan Suardana; Yohanes Kristianto (Pusat Kajian Bali Universitas Udayana, 2022)
This research aimed to analize tourist satisfaction and trust in influencing tourist behavior intentions of visiting tourists to Nusa Penida Island Klungkung Bali during the Covid-19. The theory of consumer behavior is used with several concepts namely concept of destination attributes, trust, perceived risk, and behavioral intentions of tourists. This research was designed with a quantitative approach with a survey method of 100 foreign tourists visiting Nusa Penida. The data were analized by Partial Least Square (PLS). The results show that tourism attributes have a positive and significant effect on tourist trust revisit intentions. The tourist trust has a positive significant effect on revisit intentions. Perceived risks have a positive and significant effect on tourist trust and revisit intentions. This research foud out that tourists traveling do not want to take the risk in these activities. Based on these results, it can be suggested to increase the role of trust in mediating the relationship between perceived risk and revisit intention.